Arbuscular mycorrhizal fungi alleviate salinity stress in peanut: Evidence from pot‐grown and field experiments. (12th July 2021) - Qin, Wenjie; Yan, Hengyu; Zou, Bingyin; Guo, Runze; Ci, Dunwei; Tang, Zhaohui; Zou, Xiaoxia; Zhang, Xiaojun; Yu, Xiaona; Wang, Yuefu; Si, Tong
Abstract: Arbuscular mycorrhizal fungi (AMF) species are essential for sustainable agriculture of legume crops; however, the AMF response in legume crops, especially from the perspective of physiological and molecular mechanisms under salinity conditions, is largely unknown. In this study, peanut ( Arachis hypogaea L.) seeds were inoculated with AMF to investigate its salinity stress alleviation effects using the pot‐grown and 2‐year field experiments. Seeds from two peanut cultivars (HY22 and HY25) were inoculated with AMF Rhizophagus irregularis SA and Funneliformis mosseae BEG95 (1:1), and the physiological and transcriptional responses were compared between the AMF‐inoculated and non‐inoculated peanut plants. Under the salinity stress, compared with the control samples, the AMF‐inoculated plants showed higher net photosynthetic rate, leaf relative water content (RWC), plant height, osmolyte accumulation, but lower leaf relative electrolyte conductivity (REC). Also, the malondialdehyde (MDA) concentration was reduced while the antioxidant enzymes such as superoxide dismutase (SOD), guaiacol peroxidase (G‐POD), catalase (CAT), and ascorbate peroxidase (APX) were activated. Furthermore, transcriptome data revealed that AMF potentially alleviates salt stress by regulating redox processes, cell wall assembly, cell growth, and other similar processes. In the 2‐year field experiment, AMF‐inoculated peanut seeds of HY22 and HY25 were cultivated in both non‐saline and saline soils. Under salinity conditions, AMF inoculation induced the total protein concentration by 11.11 and 2.32% in kernels and further increased the peanut pod yield by 21.83 and 21.89% in HY22 and HY25, respectively. In non‐saline soil too, AMF increased the peanut pod yield by 11.47 and 23.98% in HY22 and HY25, respectively. Taken together, these results strongly demonstrate that the combination of AMF Rhizophagus irregularis SA and Funneliformis mosseae BEG95 (1:1) can alleviate salinity stress in peanuts by improving plant growth, photosystem, and antioxidant system. Additionally, it increases the peanut pod yield under both normal and salinity conditions. Abstract : Combined with physiological and transcriptome analysis, the present study was carried out using both pot‐grown and 2‐year field experiments with two peanut cultivars. We demonstrate that seed priming with AMF Rhizophagus irregularis SA and Funneliformis mosseae BEG95 (1:1) could alleviate salinity stress in peanut by improving plant growth, regulating the photosystem, strengthening the antioxidant system, and further increasing the pod yield.